Penerapan Standar Akuntansi Keuangan UMKM Dalam Penyusunan Laporan Keuangan Pada Usaha Mikro Kecil Menengah Di Kota Batam - Anggita Dwi Putri Ayu; Haposan Banjarnahor (Prosiding, 2023)
Micro, small and medium enterprises are businesses that have received attention from the Indonesian government. Financial reports are generally up to standard SAK EMKM, including notes on the statement of financial position, income statement and notes on financial statements. The main objective of the study is the accounting records of business actors in Batam City who have implemented financial accounting standards for micro, small and medium enterprises. Motivation for financial reports, socialization will be significantly related to the implementation of MSMEs. This approach uses qualitative interviews and questionnaires distributed to 100 respondents. Based on the data processing carried out on the variable financial statement variable (X1), the statement X1-X6 has a positive value. The conclusion is that the financial statements of micro, small and medium enterprises have a significant effect on SAK EMKM.